Drug Safety Evaluation Methods and Protocols - Gautier, Jean-Charles.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Non-clinical drug safety evaluation, the assessment of the safety profile of therapeutic agents through the conduct of laboratory studies in in vitro systems and in animals, is an essential step in the progress of new pharmaceuticals heading toward the ultimate goal of clinical trials and, eventually, approval. In Drug Safety Evaluation: Methods and Protocols, expert researchers detail a compendium of analytical technologies with a focus on clarity and applicability in real life laboratory practice. These meticulous contributions feature key topics such as acute to chronic general toxicity studies, histopathology studies, reproductive toxicity studies, genotoxicity studies, safety pharmacology studies, investigative toxicity studies, and safety biomarker studies. As a volume in the highly successful Methods in Molecular Biology™ series, chapters include brief introductions to their respective subjects, lists of the necessary materials, step-by-step, readily reproducible protocols, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and authoritative, Drug Safety Evaluation: Methods and Protocols serves as an ideal guide to this field, helpful to pharmaceutical scientists, toxicologists, biochemists, and molecular biologists as well as scientists from all other disciplines who wish to translate these thorough methods into their own work.
Developing Combination Drugs in Preclinical Studies -- Preclinical Evaluation of Juvenile Toxicity -- Necropsy and Sampling Procedures in Rodents -- Histopathology Procedures: From Tissue Sampling to Histopathological Evaluation -- Principles and Methods of Immunohistochemistry -- Tissue Microarrays and Digital Image Analysis -- Micronucleus Assay and Labeling of Centromeres with FISH Technique -- The Use of Bacterial Repair Endonucleases in the Comet Assay -- Manual Whole-Cell Patch-Clamping of the HERG Cardiac K+ Channel -- Generation and Analysis of Transcriptomics Data -- Protocols of Two-Dimensional Difference Gel Electrophoresis (2D-DIGE) to Investigate Mechanisms of Toxicity -- Protocols and Applications of Cellular Metabolomics in Safety Studies Using Precision-Cut Tissue Slices and Carbon 13 NMR -- Statistical Analysis of Quantitative RT-PCR Results -- Evaluation of Mitochondrial Respiration in Cultured Rat Hepatocytes -- FETAX Assay for Evaluation of Developmental Toxicity -- Evaluation of Embryotoxicity Using the Zebrafish Model -- Protocols of In vitro Protein Covalent Binding Studies in Liver -- Utilization of MALDI-TOF to Determine Chemical-Protein Adduct Formation In vitro -- Utilization of LC-MS/MS Analyses to Identify Site-Specific Chemical Protein Adducts In vitro -- 1-Dimensional Western Blotting Coupled to LC-MS/MS Analysis to Identify Chemical-Adducted Proteins in Rat Urine -- Identification of Chemical Adducted Proteins in Urine by Multi-Dimensional Protein Identification Technology (LC/LC-MS/MS) -- Optimization of SELDI for Biomarker Detection in Plasma -- Differential Proteomics Incorporating iTRAQ Labelling and Multi-Dimensional Separations -- NMR and MS Methods for Metabonomics -- Absolute Quantification of Toxicological Biomarkers by Multiple Reaction Monitoring.
Keywords: Pharmacology; Laboratory medicine; Pharmacology/Toxicology.; Laboratory Medicine